The Effectiveness of the Paradoxical Timetable Cure on Self-Objectification and the Experience of Close Relationships in Women with Low Psychological Capital Diagnosed with Anuptaphobia - Feyzi , Faezeh; Anasseri, Mehryar (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aimed to evaluate the effectiveness of the Paradoxical Timetable Cure on self-objectification and the experience of close relationships in women with low psychological capital diagnosed with anuptaphobia. Methods and Materials: This quasi-experimental study employed a pretest-posttest control group design. The statistical population consisted of women with low psychological capital diagnosed with anuptaphobia who sought psychological treatment at the "Lost Piece" Counseling Center in Tehran in 2024. Using purposive non-random sampling, 24 participants were selected and randomly assigned to an experimental group (n = 12) and a control group (n = 12). The experimental group underwent six 60-minute sessions of the Paradoxical Timetable Cure, while the control group received no intervention. After attrition, the final sample included 10 participants in each group. Data were collected using the Self-Objectification Questionnaire, the Revised Experience in Close Relationships Questionnaire, and the Hedges Psychological Capital Scale. Data analysis was performed using multivariate and univariate analyses of covariance (MANCOVA and ANCOVA) in SPSS software. Findings: The results showed significant differences between the experimental and control groups in posttest scores for both self-objectification and experience of close relationships. The Paradoxical Timetable Cure significantly reduced self-objectification scores (F = 12.829, p = .001, η² = .658) and increased experience of close relationships (F = 10.013, p = .001, η² = .667). Conclusion: The findings suggest that the Paradoxical Timetable Cure is an effective psychological intervention for reducing self-objectification and improving the experience of close relationships in women with low psychological capital diagnosed with anuptaphobia.